Family, Authority, and Democracy: A Legacy of Critical Theory - Sembler, Camilo (Revista de Sociología, 2023)
The family has often been treated as an institution that is rather distant from the concerns that are proper to a theory of democracy. In this article, I elaborate on the idea that an important legacy of Critical Theory consists of situating the question of the family in relation to phenomena such as authoritarianism and democracy. First, I reconstruct some key features of the approach to the family that were developed early on in Studies on Authority and the Family. Next, I examine the way in which the family is approached by important contemporary exponents of this tradition, such as Jürgen Habermas, Nancy Fraser, and Axel Honneth. Finally, I briefly return to the question of the relevance of the legacy of Critical Theory in this field.